2003
DOI: 10.1177/1066480702250146
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Enhancement Couples and Family Outcome Research of the Last 20 Years

Abstract: Twenty years of outcome research conducted on Relationship Enhancement (RE) couples and family therapy are reviewed. Studies testing RE with premarital and marital couples as well as special populations are included. Effect sizes are included to provide further information on the comparison of treatment to control groups. Implications for practitioners and research are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…For example, The Prevention Relationship Education Program (PREP) focuses on paraphrasing partner statements to avoid common pitfalls of mindreading, blaming, etc. (Markman, Stanley & Blumberg, 2010), whereas Relationship Enhancement focuses on the importance of empathy and how to effectively communicate understanding to one’s partner (Accordino & Guerney, 2003). While both interventions focus on communication, the subtle differences between paraphrasing and empathy are important when testing for mechanisms.…”
Section: General Perspectives On Mechanisms Of Changementioning
confidence: 99%
“…For example, The Prevention Relationship Education Program (PREP) focuses on paraphrasing partner statements to avoid common pitfalls of mindreading, blaming, etc. (Markman, Stanley & Blumberg, 2010), whereas Relationship Enhancement focuses on the importance of empathy and how to effectively communicate understanding to one’s partner (Accordino & Guerney, 2003). While both interventions focus on communication, the subtle differences between paraphrasing and empathy are important when testing for mechanisms.…”
Section: General Perspectives On Mechanisms Of Changementioning
confidence: 99%
“…It also teaches listening skills involving the understanding and acceptance of the self-discloser's statements (Ridley & Sladeczek, 1992). Nine skills are taught: empathic, expressive, discussion and negotiation, problem-conflict resolution, facilitation (partner coaching), self-change, other change, transfer generalization, and maintenance (Accordino & Guerney, 2003). The format for RE ranges from all-day marathon sessions to the more common format of a group meeting 2 hours weekly for 10-15 weeks.…”
Section: Efficacious Programsmentioning
confidence: 99%
“…A meta-analysis conducted on several enrichment programs showed RE to have the largest effect size of all programs reviewed (Giblin et al, 1985). A recent review of RE's outcome research (Accordino & Guerney, 2003) found that RE groups experienced higher levels of marital communication and increased self-esteem than control groups. Clearly, research has shown Relationship Enhancement to be an efficacious program for marital enhancement.…”
Section: Efficacious Programsmentioning
confidence: 99%
“…Being empathic or understanding the point of view of a partner, seemed to be facilitated as individuals observed their taped interaction. Programs that specifically teach individuals to be more empathic such as Bernard Guerney's Relationship Enhancement Program (Accordino & Guerney, 2003; Cavedo & Guerney, 1999) may benefit from utilizing this videotaping methodology.…”
Section: Discussionmentioning
confidence: 99%